APUCEN IN ACTION TO SUPPORT SURVIVORS OF TYPHOON PABLO IN ANDAP, PHILIPPINES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
ANDAP, PHILIPPINES, 7 March 2016 Universiti Sains Malaysia (USM) through the AsiaPacific UniversityCommunity Engagement Network (APUCEN) once again made its presence felt when it attended the groundbreaking ceremony, held in Andap, Philippines, recently to mark the commitment to build 10 permanent shelters for survivors of Typhoon Pablo, which hit Andap on December 4, 2012.